DESKRIPTIF MALE FEMINISME DAN KONTRA MALE FEMINISME PERILAKU TOKOH PRIYAYI GOLONGAN NINGRAT JAWA DALAM NOVEL POSKOLONIAL INDONESIA - Bambang Aris Kartika (LITERASI: Indonesian Journal of Humanities, 2011)
Patriarchal culture is synonymous with the hegemonic power of the Javanese nobility, especially from the class of nobles, to the position of Javanese women, particularly those related to the ongoing gender inequality. However, in the perspective of deconstruction are the concepts of binary op position, if there are any cons there are also male male feminism feminism, namely the aristocratic Javanese culture of patriarchy that does not apply to conduct in order to hegemonic power and control the subordinate position of women. In the novel De Winst binary opposition between male feminism with male counter feminism is reflected in the behavior of male figures from the Javanese aristocratic class of nobles in court environments Surakata Sultanate Palace that strong tradition to uphold patriarchy and feudalism on the position of women, especially in the period of colonialism Dutch and Javanese monarchy system. Keywords: male feminism, male counter feminism, cultural patriarchy, feudalism